Non-extractable polyphenols in tropical fruits: Occurrence and health-related properties - Reynoso Camacho, Rosalía (2018)
Tropical fruits are good sources of phenolic compounds. Mango, pineapple, papaya and avocado are among the most commercialised tropical fruits worldwide. Tropical fruits with higher extractable polyphenol (EPP) contents include camu–camu, acerola and assai. Fruits with high contents of non-extractable polyphenols (NEPP) include cashew apple, banana and tropical blackberry, followed by acerola, plantain, melon, mango and papaya. Among the identified NEPP are gallocatechin in banana, sanguiin H-6, lambertianin C and galloyl derivatives in tropical blackberries and oligomers, mainly O-galloyl-glucosides, in mango. There are few studies of the antioxidant capacities (AC) of NEPP of tropical fruits, and most of the reports are for Brazilian fruits. Hydrolysable polyphenols from assai and non-extractable proanthocyanidins and HPP associated with insoluble dietary fibre from cashew apple show the highest AC values in comparison with other Brazilian fruits. Some biological activities of tropical fruits are related to ellagitannins, which are metabolised by microbiota, releasing ellagic acid and urolithins. The principal biological activities associated with phenolic compounds are antioxidant, anti-inflammatory, antidiabetic, antiproliferative, antimicrobial and hypolipidaemic properties. Tropical fruits are rich in NEPP, and this opens prospects for their use in industry. Further studies are needed to elucidate their health-related properties and obtain access to new markets.